Топливное устройство ядерного реактора - Гаврилов П. М. Петр Михайлович; Дмитриев А. М.; Кохомский А. Г.; Мещеряков В. Н.; Шидловский В. В. Владимир Владиславович; Цыганов А. А.; Чуканов В. Б.
опубл. 27.05.05